2014
DOI: 10.5539/elt.v7n2p144
|View full text |Cite
|
Sign up to set email alerts
|

Age Differences in the Use of Language Learning Strategies

Abstract: The purpose of the study was to investigate language learning strategies used by English as a Foreign Language (EFL) learners at different educational levels and explored the influence of age on the use of language learning strategies. A total of 1,023 students participated in the study. Out of the participants, there were 250 primary students (aged 10-12), 245 junior high school students (aged 13-15), 249 senior high school students (aged 16-18), and 279 tertiary students (aged 20-22). The instrument for data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 21 publications
2
21
1
2
Order By: Relevance
“…Новији резулOаOи још је9но: ис@иOивања сOраOе:ија у исOој сре9ини (Cheng, 2014) @оказују 9а ученици нижих разре9а основ-не школе у мањој мери @римењују ком@ензационе сOраOе:ије не:о сOарији ис@иOаници, 9ок у већој мери @римењују мемориј-ске сOраOе:ије, као и меOако:ниOивне које су ко9 њих ран:иране на @рвом месOу. МеOако:ниOивне сOраOе:ије су најчешће @риме-њиване сOраOе:ије и ко9 је9анаесOо:о9ишњих ученика у Мађар-ској, @рема резулOаOима је9но: исOраживања с@рове9ено: у Oој сре9ини (Doró & Habók, 2013).…”
Section: истраживања примене стратегија за учење страног језика код уunclassified
See 1 more Smart Citation
“…Новији резулOаOи још је9но: ис@иOивања сOраOе:ија у исOој сре9ини (Cheng, 2014) @оказују 9а ученици нижих разре9а основ-не школе у мањој мери @римењују ком@ензационе сOраOе:ије не:о сOарији ис@иOаници, 9ок у већој мери @римењују мемориј-ске сOраOе:ије, као и меOако:ниOивне које су ко9 њих ран:иране на @рвом месOу. МеOако:ниOивне сOраOе:ије су најчешће @риме-њиване сOраOе:ије и ко9 је9анаесOо:о9ишњих ученика у Мађар-ској, @рема резулOаOима је9но: исOраживања с@рове9ено: у Oој сре9ини (Doró & Habók, 2013).…”
Section: истраживања примене стратегија за учење страног језика код уunclassified
“…ИсOи у@иOник @римењиван је и у 9ру:им исOражива-њима ово: Oи@а у скраћеној (Doró & Habók, 2013;Lan & Oxford, 2003) или @уној верзији (Chen, 2009;Cheng, 2014;Lee & Oxford, 2008). Иако је у@иOник коришћен и 9ве :о9ине раније, @реO@о-сOавка исOраживача Lила је 9а Oај @о9аOак нема уOицаја на резул-OаOе, а 9а ће се @рименом исOо: инсOруменOа 9оLиOи вали9нији @о9аци.…”
Section: методологија истраживањаunclassified
“…Being well studied, the problem of borrowings can still find reflections in researchers in the field of a second language acquisition, as well as in studying the influence of the age on the acquisition of a foreign language (Chen, 2014). Different educational levels and occupation are also of great importance for our future work basing on the conducted study.…”
Section: Introductionmentioning
confidence: 97%
“…Echoing the previous international studies, different variables have been found to affect LLS across learner groups in the context of Taiwan. For example, investigations by Chang, Liu, and Lee (2007) and Chang (2011) identified significant differences in strategy use according to gender and academic major, according to age, as found by Chen (2014), grade level (Chen, 2009), ethnic group (Yang, 2007), proficiency level (Lai, 2009;Wu, 2008), motivation (Lan & Oxford, 2003), and learner beliefs (Yang, 1999). Almost all of these studies came to the conclusion that Taiwanese EFL learners are low to medium strategy users, with average scores ranging from 2.5 to 3.4 out of a total of 5.…”
Section: Taiwanese Efl Learners' Llsmentioning
confidence: 99%
“…Hence, the number of CLIL courses/programmes, all of which are delivered in English only, is growing at a fast rate. Studies evaluating CLIL programmes and their positive effects on learners' achievements have recently been carried out (Yang, 2015(Yang, , 2017a(Yang, , 2017bYang & Gosling, 2013, 2014. However, there is still a need for a thorough and deeper investigation of which strategy types are deployed by CLIL learners to approach both content and language learning via English in Taiwan's CLIL educational context, to better understand which strategies account for the initial success of the approach.…”
Section: Wenhsien Yangmentioning
confidence: 99%